Khulafaurrasyidin in the Shadow of Conflict: a Critical Study of the Transition of Power After the Prophet - Yosa Wananda; Kholid Mawardi (STKIP Taman Siswa Bima, 2025)
This study aims to critically examine the historical dynamics of the Khulafaur Rasyidin period as the initial phase of the formation of the Islamic government system. The four caliphs Abu Bakar, Umar, Uthman, and Ali ruled in a highly diverse and tense socio-political context. Analysis shows that this period was not entirely stable and harmonious, but rather fraught with internal crises such as elite conflicts, regional rebellions, and social fragmentation. Uthman bin Affan's leadership was marked by nepotism and public discontent that sparked open rebellion, while Ali bin Abi Talib's reign took place amid civil war and the emergence of armed opposition movements such as the Khawarij. This study utilises a historical-critical approach with classical Islamic sources and narrative analysis of power dynamics to demonstrate that the history of the Khulafaur Rasyidin needs to be understood in a more contextual manner. The results of this research are expected to enrich the discourse on Islamic political history by emphasising the importance of examining the complexity of social realities and the challenges of post Prophet governance.